2012
DOI: 10.1111/j.1745-459x.2012.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Preference for Tactile Softness: A Question of Affect Intensity?

Abstract: Previous studies have shown that consumers with higher affect intensity expressed stronger preferences for softer car seat fabrics (Kergoat et al.). The present research aims to consolidate and expand these results. Across two studies, we attempt to determine whether the intensity of affect (as measured by the affect intensity measure; Larsen) is a more general construct involved in soft textile preferences. Through the evaluation of two product categories (car seat fabrics and washed‐shirt fabrics) and the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 56 publications
1
30
0
Order By: Relevance
“…Personality traits, which relate to the “content” of behavior (Kergoat et al . ), tend to be stable over time where emotions are more transient (Revelle and Scherer ). Personality relates to the content of behavior, as opposed to emotion, which refers to the way a person behaves.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Personality traits, which relate to the “content” of behavior (Kergoat et al . ), tend to be stable over time where emotions are more transient (Revelle and Scherer ). Personality relates to the content of behavior, as opposed to emotion, which refers to the way a person behaves.…”
Section: Introductionmentioning
confidence: 99%
“…Kergoat et al . () suggested that using sociodemographic, economic measures, or usage/attitude questionnaires commonly provided insufficient information for understanding consumer preference. However, a study of consumer affect intensity and psychological properties (e.g., personality) would provide a better explanation to research scientists for understanding psychological components involved in fabric preferences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent to which measurements are repeatable depends on the sources of variance that are considered relevant in a study. Removing ambiguous or unfamiliar words from self-report questionnaires to mitigate variance as it is suggested by Barnes and Lilford [24] as well as minimal sensory variation in the perceptual task excepting the experimental stimuli as it is recommended by Kergoat and colleagues [32] are important actions in tests. Nevertheless, there will be no guarantee that the relative differences between numbers assigned to the scores would represent measures of people's impressions.…”
Section: Discussionmentioning
confidence: 99%
“…Another dimension of tactile comfort which should be considered is affect intensity. By studying consumer preference for different textile having different sensory attributes, Kergoat et al (2012) reported that affect intensity plays a role in consumer soft textile preference. The aforementioned study involved car seats and shirts, cover both positive and negative emotions and was limited to fabric softness.…”
Section: Fabric Properties Affecting Sensorial Comfortmentioning
confidence: 99%